Intercultural education and literacy : an ethnographic study of indigenous knowledge and learning in the Peruvian Amazon - Aikman, Sheila (Studies in written language and literacy, 1999)
Indigenous peoples around the world are calling for control over their education in order to reaffirm their identities and defend their rights. In Latin America the indigenous peoples, national governments and international organisations have identified intercultural education as a means of contributing to this process. The book investigates education for and by indigenous peoples and examines the relationship between theoretical and methodological developments and formal practice. An ethnographic study of the Arakmbut people of the Peruvian Amazon, provides a detailed example of the social, c.